(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: The objective of this study is to compare the frequency of inguinal hernia repair performed under local and spinal anesthesia as a day-case surgery. Study Design: Randomized Controlled Trial Setting: Surgical Unit-II, Sir Ganga Ram Hospital, Lahore Subject and Methods: Hundred patients fulfilling the inclusion criteria were selected for study; they were divided into two groups by random number table. In group A hernia repair was done under spinal anesthesia and in group B repair was done under local anesthesia. Spinal anesthesia was given by anesthetist and local anesthesia was given by same team of surgeons. Mesh hernioplasty was performed in all the 100 patients. Patients were discharged when they were pain free (Visual Analogue Scale (VAS<3) and passed urine. Total time period from operation till the time of discharge was noted. Results: In this study rate of day cases in inguinal hernia repair done under local anesthesia was 84 %( 42 /50 patients discharged as day cases), while in spinal anesthesia was 68 %( 34/50 discharged as day cases). Conclusion: Inguinal hernia repair under local anesthesia is safe and feasible. It has shorter duration of hospital stay, lesser urinary complications and more post-operative analgesia resulting in elective inguinal hernia surgery as a day-case.